2007
DOI: 10.1074/jbc.m608074200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Actin Cytoskeleton-dependent and -independent Pathways for RelA/p65 Nuclear Translocation in Endothelial Cells

Abstract: Activation of the transcription factor NF-B involves its release from the inhibitory protein IB␣ in the cytoplasm and subsequently, its translocation to the nucleus. Whereas the events responsible for its release have been elucidated, mechanisms regulating the nuclear transport of NF-B remain elusive. We now provide evidence for actin cytoskeleton-dependent and -independent mechanisms of RelA/p65 nuclear transport using the proinflammatory mediators, thrombin and tumor necrosis factor ␣, respectively. We demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
63
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 58 publications
(60 reference statements)
8
63
0
Order By: Relevance
“…Whether the specific mechanism involves an interaction of VASP directly with NF-B or with upstream signaling molecules is unknown, and several possibilities exist. For one, VASP regulates actin polymerization (17), and the actin cytoskeleton may in turn regulate NF-B translocation to the nucleus in response to thrombin (5). This model is consistent with the dynamic nature of the actin cytoskeleton and the fact that its polymerization and depolymerization are critical determinants of many cellular responses, including inflammatory activation.…”
Section: Discussionsupporting
confidence: 65%
“…Whether the specific mechanism involves an interaction of VASP directly with NF-B or with upstream signaling molecules is unknown, and several possibilities exist. For one, VASP regulates actin polymerization (17), and the actin cytoskeleton may in turn regulate NF-B translocation to the nucleus in response to thrombin (5). This model is consistent with the dynamic nature of the actin cytoskeleton and the fact that its polymerization and depolymerization are critical determinants of many cellular responses, including inflammatory activation.…”
Section: Discussionsupporting
confidence: 65%
“…The possibility that transcriptional activity of NF-B may depend on arrangement of the cytoskeleton has been previously proposed by Mackenzie et al (27), who found that cytoskeletal integrity is essential for the nuclear translocation of NF-B in neuronal cells. Moreover, Fazal et al (10) reported that actin dynamics play a role in thrombin-induced nuclear uptake of RelA/p65 in endothelial cells. Although the mechanism by which the actin cytoskeleton participates in regulating NF-B signaling remains unclear, several possibilities are open to speculation.…”
Section: Discussionmentioning
confidence: 99%
“…That EVM150 inhibits NF-B independently of the kelch domain and cullin-3 is not surprising since proteins containing BTB domains regulate a wide variety of cellular processes, including transcriptional regulation and cytoskeletal rearrangement (66)(67)(68). Interestingly, it has recently been demonstrated that NF-B nuclear translocation relies on rearrangement of the actin cytoskeleton after degradation of IB␣ (69)(70)(71). Consequently, it is possible that EVM150 may interact with or degrade cellular BTB/kelch proteins regulate the actin rearrangement following release of NF-B from IB␣, thus inhibiting nuclear translocation.…”
Section: Discussionmentioning
confidence: 99%